DOI: 10.18297/etd/1241
|View full text |Cite
|
Sign up to set email alerts
|

CFD modeling of entrance and exit geometries of a wind speed accelerator.

Abstract: Current wind power technology is not economically feasible throughout most of the United States due to low average wind speeds. A design for a small-scale wind concentrator device suitable for use in areas of low wind velocity was tested using computational fluid dynamics (CFD). Using a novel approach, the device seeks to accelerate incoming air above minimum velocities required for economical power generation. The novel approach employs a funnel shaped inlet with relief vents along the circumference, so as to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…While designing the concentrator, this procedure for model creation and data collection proved effective in all cases. Some parts of the inlet and exit geometry were tested jointly as part of a separate project, and some results of both are presented here to completely describe the evolution of the overall design (Russ, 2011). The first item addressed was finding an optimized intake geometry.…”
Section: Viewing Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While designing the concentrator, this procedure for model creation and data collection proved effective in all cases. Some parts of the inlet and exit geometry were tested jointly as part of a separate project, and some results of both are presented here to completely describe the evolution of the overall design (Russ, 2011). The first item addressed was finding an optimized intake geometry.…”
Section: Viewing Resultsmentioning
confidence: 99%
“…These models were run with the new equation set (Russ, 2011) and it was concluded that the third or fourth curve was the best designs for the inlet. These curves showed an acceleration of 15%, from the ambient flow of 2 m/s to 2.3 m/s in the device throat, with a turbulent model…”
Section: Throat Velocities With Varying Geometriesmentioning
confidence: 99%